Can forensic and investigation audit and whistleblowing detect fraud during the Covid-19 pandemic? - Muh. Syahru Ramadhan; Mulyati (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2022)
This study aims to determine the effect of forensic audits, investigative audits, and whistleblowing on fraud detection during the COVID-19 pandemic. The sample in this study were auditors working at BPKP, BPK, and Inspectorate with a total of 90 respondents who were taken by purposive sampling method. The research data was tested using multiple regression tests. This study found that the characteristics of a forensic audit consisting of independence, objectivity, and professional skepticism can influence fraud detection. In addition, investigative audits consisting of experience and capabilities as well as whistleblowing variables have also been shown to influence fraud detection during the COVID-19 pandemic. Based on the overall results of the study, fraud detection during the COVID-19 pandemic can be improved by various strategies, especially from the internal side, namely the quality of an auditor. Various efforts can be made, namely increasing independence, objectivity, and professional skepticism as well as maximizing the ability of auditors in carrying out audit assignments. Another factor, namely the implementation of a whistleblowing system is also important in supporting the implementation and performance of auditors in accordance with the current pandemic conditions. From a theoretical point of view, quantitative research to detect fraud related to forensic audits and whistleblowing during the COVID-19 pandemic is still very limited, so the results of this study can add to the literature.